Ablative Treatments for Small Renal Masses and Management of Recurrences: A Comprehensive Review - Achille Aveta; Vincenzo Iossa; Gianluca Spena; Paolo Conforti; Giovanni Pagano; Fabrizio Dinacci; Paolo Verze; Celeste Manfredi; Matteo Ferro; Francesco Lasorsa; Lorenzo Spirito; Luigi Napolitano; et al. (Life, 2024)
This review focuses on ablative techniques for small renal masses (SRMs), including radiofrequency ablation (RFA), cryoablation (CA), microwave ablation (MWA), and irreversible electroporation (IRE), and discusses recurrence management. Through an extensive literature review, we outline the procedures, outcomes, and follow-up strategies associated with each ablative method. The review provides a detailed examination of these techniques—RFA, CA, MWA, and IRE—elucidating their respective outcomes. Recurrence rates vary among them, with RFA and CA showing comparable rates, MWA demonstrating favorable short-term results, and IRE exhibiting promise in experimental stages. For managing recurrences, various strategies are considered, including active surveillance, re-ablation, or salvage surgery. Surveillance is preferred post-RFA and post-CA, due to slow SRM growth, while re-ablation, particularly with RFA and CA, is deemed feasible without additional complications. Salvage surgery emerges as a viable option for larger or resistant tumors. While ablative techniques offer short-term results comparable to surgery, further research is essential to understand their long-term effects fully. Decisions concerning recurrence management should consider individual and tumor-specific factors. Imaging, notably contrast-enhanced ultrasounds, plays a pivotal role in assessing treatment success, emphasizing the necessity of a multidisciplinary approach for optimal outcomes. The lack of randomized trials highlights the need for further research.